Obszary oceny aktywności zabezpieczeniowej instytucji poręczeń kredytowych dla małych i średnich przedsiębiorstw a rola ich rachunkowości - Adamek, Jacek (The Areas for Hedging Activity Assessment of Credit Guarantee Institutions for SME versus the Role of Their Accountancy, 2006)
The analysis of hedging entities activity results encounters numerous obstacles of methodological, economic or political nature. The research may be carried out within the area of effects obtained by particular parties of the guarantee relationship or it may be associated with evaluating assessments in the cross-section of results and their measures such as: relevance, additionality, multiplying effect, effectiveness and efficiency of the carried out economic activity. Having assumed the above the objective of the paper is an attempt of characterizing the main areas of conducting analyses and presenting assessments of guarantee entities activity as well as indicating the role which should be assigned to accountancy of the hedging institutions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 11-20